2018
DOI: 10.1021/acs.energyfuels.7b03382
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Postsynthetic Functionalization of Tetraethylenepentamine onto MIL-101(Cr) for Separation of CO2from CH4

Abstract: To remove CO2 from CH4, tetraethylenepentamine was grafted onto coordinatively unsaturated centers of MIL-101­(Cr) by postsynthetic functionalization: wet impregnation at 298 K, followed by grafting, drying, and washing. Compared to MIL-101­(Cr), TEPA–MIL-101­(Cr) showed 54% higher CO2 adsorption at 1 bar and 98% reduction of CH4 adsorption at 60 bar. The ideal adsorption solution theory (IAST) selectivity of CO2/CH4 for a binary gas mixture of 2% CO2 + 98% CH4 at 298 K and 60 bar predicted by the Toth equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…During the grafting process, TEPA forms the dative bond with CUS of MIL-101 through the primary amine site and therefore the remaining amines would contribute in CO 2 adsorption. This will provide strong affinity between CO 2 molecules and CO 2 -philic sites (amine groups) that results in the formation of carbamate . The chemical reaction that occurs between CO 2 and amine functional groups can be expressed as follows Unlike CO 2 that adsorbs through the chemisorption mechanism, N 2 is a nonreactive gas molecule with lower quadrupole moment and polarizability than CO 2 that adsorbs only through the physisorption mechanism .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the grafting process, TEPA forms the dative bond with CUS of MIL-101 through the primary amine site and therefore the remaining amines would contribute in CO 2 adsorption. This will provide strong affinity between CO 2 molecules and CO 2 -philic sites (amine groups) that results in the formation of carbamate . The chemical reaction that occurs between CO 2 and amine functional groups can be expressed as follows Unlike CO 2 that adsorbs through the chemisorption mechanism, N 2 is a nonreactive gas molecule with lower quadrupole moment and polarizability than CO 2 that adsorbs only through the physisorption mechanism .…”
Section: Resultsmentioning
confidence: 99%
“…This will provide strong affinity between CO 2 molecules and CO 2philic sites (amine groups) that results in the formation of carbamate. 47 The chemical reaction that occurs between CO 2 and amine functional groups can be expressed as follows 48 ∫…”
Section: Synthesis Of Mil-101(cr)mentioning
confidence: 99%
“…To enable an efficient capture process for enclosed environments, it is crucial to select an adsorbent that exhibits sharp adsorption uptake at ultralow pressures. Recently, through structure modification and subsequent amine functionalization, Darunte et al demonstrated the applicability of polyethylenimine (PEI)-impregnated MIL-101 for dilute CO 2 capture. It was shown that 85 wt % PEI impregnation yields 1.0 mmol/g CO 2 adsorption capacity at 400 ppm .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the metal–organic frameworks (MOFs) material, with high specific surface area, tunable and large pore size, and diversity open metal sites, are showing great application potential of gas separation, sensing, energy storage and catalysis . Especially in the field of hydrogen storage, these properties facilitate the adsorption of H 2 on the surface of it.…”
Section: Introductionmentioning
confidence: 99%